Religiosity as a moderator of ADHD-related antisocial behaviour and emotional distress among secular, religious and Ultra-Orthodox Jews in Israel. (June 2022) - Novis-Deutsch, Nurit; Dayan, Haym; Pollak, Yehuda; Khoury-Kassabri, Mona
Background: ADHD predicts higher levels of antisocial behaviour and distress while religiosity is related to lower levels of both. This raises the hitherto unexplored question of how these variables interact. Aims: The objective of this study was to explore how religious individuals with ADHD fare in terms of these psychosocial outcomes. Method: 806 secular, religious and Ultra-Orthodox Jewish adults in Israel completed measures of ADHD symptoms and treatment, emotional strengths and difficulties, religious belonging, religious behaviour and antisocial behaviour. Results: Findings supported an additive-interactive model in which religiosity (a) correlates with lower levels of ADHD symptoms and diagnosis, (b) directly relates to less antisocial behaviour and less distress and (c) moderates the negative effects of ADHD on antisocial behaviour and distress. Findings further suggest that religious observance rather than religious belonging drives most of the moderating effect of religiosity, while religious belonging rather than religious observance drives negative attitudes towards ADHD. Conclusions: Implications include the importance of treating religious individuals with ADHD in a more nuanced manner and of providing more information on ADHD to religious communities.